SENI pertunjukan Indonesia pasca orde baru / Barbara Hatley...[et al] ; editor Barbara Hatley, G. Budi Subanar, Yustina Devi Ardhiani ; penerjemah Alwi Atma Ardhana, Lisistrata Lusandiana. - Alwi Atma Ardhana; Budi Subanar, G.; Hatley, Barbara; Lisistrata Lusandiana; Yustina Devi Ardhiani (Universitas Sanata Dharma, 2014)
x, 327 hlm. : ilus. ; 23 cm